Workshop report: Integrated Modeling of Climate Impacts on Agricultural Productivity and Socio-Economic Status (IMCASE) in the Philippines - Sheinkman, Michael (2015)
CCAFS and IRRI jointly organized a workshop on potential uses of integrated modelling of Agricultural Productivity and Socio-Economic status on 3-5 September 2013 at IRRI campus, Los Banos, Philippines. The workshop was attended by participants from global, regional, and national institutions, including: three (3) CGIAR Research Centers (CIAT, CIMMYT, and IRRI); the CGIAR Research Program on Climate Change, Agriculture, and Food Security (CCAFS); the FAO; and the government of the Republic of the Philippines (PAGASA, BAS, and NSO). Workshop presentations and discussions accomplished the following objectives: (1) present the concepts and components of Integrated Food Security Modeling and shared descriptions, methodologies, and progress of work for modeling activities currently underway in the Philippines, regionally, and globally, including climate models, bio-physical crop models, and econometric models; (2) identify challenges and uncertainties that constrain the accuracy of model outputs, including lack of access to data in formats suitable for model input, data quality issues, methods of interpolation and extrapolation used to create gridded data, and measures of uncertainty when models are combined; and (3) identify common interests and potential synergies between modeling activities along with follow-up actions in the Philippines to faciliatate use of integrated models to simulate impacts of policy options for food security and climate risk management. Institutions participating in IMCASE agree to work towards two major outcomes. First, PAGASA receives technical support needed to produce historical climate datasets and seasonal forecasts in formats compatible with model input requirements. Second, development partners, research institutions, and government agencies, mainstream the use of climate services and modelling tools for crop yield forecasting, crop monitoring, food commodity price forecasting, and food security planning and policy formulation, at national, sub-national, and local levels.